Neuromodulation via the Cerebrospinal Fluid: Insights from Recent in Vitro Studies - Bjorefeldt, Andreas; Illes, Sebastian; Zetterberg, Henrik; Hanse, Eric (Frontiers in Neural Circuits, 2018)
The cerebrospinal fluid (CSF) occupies the brain’s ventricles and subarachnoid space and, together with the interstitial fluid (ISF), forms a continuous fluidic network that bathes all cells of the central nervous system. As such, the CSF is well positioned to actively distribute neuromodulators to neural circuits in vivo via volume transmission. Recent in vitro experimental work in brain slices and neuronal cultures has shown that human CSF indeed contains neuromodulators that strongly influence neuronal activity. Here we briefly summarize these new findings and discuss their potential relevance to neural circuits in health and disease.